The empowerment puzzle: Unmasking the role of women’s empowerment in addressing undernutrition in India - Sharma, Anjali; Nihal, Saif (International Institute for Population Sciences, India, 2023)
India faces a significant challenge in addressing the target of SDGs set for nutrition for both mothers as well as children. A significant number of studies have identified that women’s empowerment plays a vital role in determining their own health and nutritional status as well as that of their children. However, the majority of studies based on the National Family and Health Survey looked at empowerment in terms of a composite index of autonomy in decision-making, autonomy in mobility, financial autonomy, and attitude toward wifebeating. This study is a valuable addition to existing research by incorporating additional indicators and investigating their individual roles in understanding the prevalence of undernutrition among mothers and children. By utilizing the latest round of the National Family and Health Survey (2019–21), women’s empowerment was assessed through five distinct dimensions: autonomy in decision-making and mobility, workforce participation, ownership of assets, attitude toward violence, and digital empowerment. Both bivariate and multivariate techniques were employed with two outcome variables (i.e., underweight children and underweight mothers). Findings indicated that the prevalence of undernutrition among both mother and children decreases with increasing autonomy index, digital empowerment, and negative attitude toward wifebeating. However, two surprising findings were identified. Firstly, the prevalence of undernutrition was higher among both mothers and children if the mother was working in the agricultural sector. Secondly, the undernutrition among children was higher if the mother had ownership of assets. This requires further investigation for pathways through which these individual dimensions of women’s empowerment play a role for determining undernutrition.